2015
DOI: 10.1111/eea.12298
|View full text |Cite
|
Sign up to set email alerts
|

Influence of native and alien Prunus species and light conditions on performance of the leaf beetle Gonioctena quinquepunctata

Abstract: The polyphagous beetle Gonioctena quinquepunctata Fabricius (Coleoptera: Chrysomelidae) is a serious leaf pest of the native European bird cherry, Prunus padus L., and the invasive alien black cherry, Prunus serotina Ehrh. (Rosaceae). In the shade, leaf damage is extensive in both species, whereas in full light, it is extensive in P. padus, but very low in P. serotina. We determined the influence of Prunus species and light conditions on differences in performance of both sexes of this folivore. In a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…In general, females of most insect species are much heavier than their male counterparts [ 43 , 44 ]. This observation was also determined to be true for female beetles in earlier studies of Gonioctena quinquepunctata [ 45 ] and Altica brevicollis coryletorum [ 14 ]. Changes in the body mass of current-year beetles of both sexes occurred as a direct result of the amount of feeding.…”
Section: Discussionsupporting
confidence: 53%
“…In general, females of most insect species are much heavier than their male counterparts [ 43 , 44 ]. This observation was also determined to be true for female beetles in earlier studies of Gonioctena quinquepunctata [ 45 ] and Altica brevicollis coryletorum [ 14 ]. Changes in the body mass of current-year beetles of both sexes occurred as a direct result of the amount of feeding.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, the same folivorous species occur for both species, but P. padus experiences a much greater loss of leaf mass as a host than does P. serotina (Karolewski et al, 2013). A variety of mono-and polyphagous insect pests, especially the leaf beetle Gonioctena quinquepunctata F. (Mąderek et al, 2015), aphid Rhopalosiphum padi L. (Halarewicz & Gabryś, 2012) and Yponomeuta evonymellus L. , have more food sources due to the presence of alien species, so their increased populations may simultaneously pose a greater risk to P. padus (as it is their primary host). In addition, the invasive P. serotina is extremely resistant (P. padus is as well, but to a lesser extent) to various leaf mass reducing factors, such as insects (Halarewicz & Jackowski, 2011), artificial defoliation (Karolewski et al, 2010), mechanical damage of branches or even complete removal of the aboveground part of shrubs (Annighöfer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, invasive Prunus serotina Ehrh. demonstrates a strong and close phylogenetic relationship with native P. padus L. (Bortiri et al 2001), and differences in food quality are small, so native specialists (Karolewski et al 2014) and generalists (Nowakowska and Halarewicz 2006;Mąderek et al 2015) have adapted to carrying out the entire life cycle with this new plant. Between Salix viminalis and Spiraea tomentosa, there is no close phylogenetic affinity, and our measurements show that the leaves of these two species differ significantly in relation to both chemical and morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…More details concerning the methods and parameters that we used in this study can be found in the literature (e.g. Waldbauer 1968;Mąderek et al 2015).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation